A framework for evaluating electronic health record vendor user-centered design and usability testing processes. (3rd July 2016) - Ratwani, Raj M; Zachary Hettinger, A; Kosydar, Allison; Fairbanks, Rollin J; Hodgkins, Michael L
Abstract : Objective: Currently, there are few resources for electronic health record (EHR) purchasers and end users to understand the usability processes employed by EHR vendors during product design and development. We developed a framework, based on human factors literature and industry standards, to systematically evaluate the user-centered design processes and usability testing methods used by EHR vendors. Materials and Methods: We reviewed current usability certification requirements and the human factors literature to develop a 15-point framework for evaluating EHR products. The framework is based on 3 dimensions: user-centered design process, summative testing methodology, and summative testing results. Two vendor usability reports were retrieved from the Office of the National Coordinator's Certified Health IT Product List and were evaluated using the framework. Results: One vendor scored low on the framework (5 pts) while the other vendor scored high on the framework (15 pts). The 2 scored vendor reports demonstrate the framework's ability to discriminate between the variabilities in vendor processes and to determine which vendors are meeting best practices. Discussion: The framework provides a method to more easily comprehend EHR vendors' usability processes and serves to highlight where EHR vendors may be falling short in terms of best practices. The framework provides a greater level of transparency for both purchasers and end users of EHRs. Conclusion: The framework highlights the need for clearer certification requirements and suggests that the authorized certification bodies that examine vendor usability reports may need to be provided with clearer guidance.